ENGLISH LEARNING SYSTEM IN ISLAMIC BOARDING SCHOOL - Ilham Nurjaman (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2013)
This research is describe the real description about English learning system in SMP Plus Al-Aqsho. This research uses qualitative research design This research intends to find out: (1) the English learning system in SMP Plus Al-Aqsha Islamic Boarding School, (2) the output of the teaching of English learning system in SMP Plus Al-Aqsha Islamic Boarding School, and (3) the supporting factors and obstacles in achieving the effectiveness of English learning system at SMP Plus Al-Aqsha Islamic Boarding School. In presenting the data, descriptive method is used in this research. Descriptive method is research method that tried to describe and interpret the object based on the real situation of that object. Techniques of collecting data in this research are observation, questionnaire, and interview. From the research, it can be concluded that with this system, the score or achievement index, expecially English subject, the students are able to comprehend the material so that they get score in average of students’ score exceed the standar from KKM. The supporting factor in learning English is the additional English subject under curriculum of KMMI, while the obstacle is the congest schedule.